Endoscopic negative pressure therapy with open-pore film drainage and open-pore polyurethane sponge drainage for iatrogenic perforation of the esophagus - Wichmann, Dörte; Stüker, Dietmar; Schempf, Ulrike; Werner, Christoph R.; Steger, Volker; Königsrainer, Alfred; Schweizer, Ulrich; Archid, Rami (Endoscopy, 2020)
Background Management of iatrogenic esophageal perforation (IEP) is challenging. Endoscopic negative pressure therapy (ENPT) is an emerging and effective tool for the treatment of gastrointestinal and anastomotic leaks. We have used ENPT as first-line therapy for IEP since 2017. The aim of this study was to present our results with this strategy in patients with IEP. Methods Nine patients were treated with ENPT for IEP between August 2017 and August 2019. Their treatment characteristics, including duration of therapy, strategy used, and outcomes, were analyzed. Treatment included ENPT with open-pore film drainage (OFD) and open-pore polyurethane foam drainage (OPD).Results Early diagnosis (< 24 hours) of IEP occurred in four patients. After a mean (standard deviation) of 19.0 (13.5) days of ENPT, 6.4 (3.4) endoscopies, and 38.1 (40.3) days of hospitalization, endoscopic treatment was effective and successful in all of the patients. Additional video-assisted thoracic surgery (VATS) was done in four patients. Conclusions ENPT is an effective new method for the management of IEP. ENPT with OFD and OPD can be combined with minimally invasive operative methods for sepsis control in IEP.